The clinical application value and the imaging characteristic of 18F-FDG PET/CT in tuberculous pericarditis - Xiaoqing Du; Feng Zhu; Qian You (BMC Cardiovascular Disorders)
Abstract Background Tuberculous pericarditis is the most common cause of pericardial disease in tuberculosis-endemic areas. Accurate and early diagnosis of tuberculous pericarditis is crucial due to its high mortality; however, the diagnostic accuracy of current methods remains suboptimal. This study aims to investigate the clinical application value and imaging characteristics of 18F-FDG PET/CT in tuberculous pericarditis. Methods A total of 11 patients with tuberculous pericarditis were retrospectively analyzed in this study. Patients were categorized into two groups based on the presence or absence of pericardial 18F-FDG uptake. Differences in clinical symptoms between the two groups were assessed using the Mann-Whitney U test. Additionally, all tuberculous lesions in lymph nodes and other organs within the scanning range were systematically evaluated. Results Tuberculous pericarditis was successfully detected by 18F-FDG PET/CT in 9 of the 11 patients, yielding a diagnostic sensitivity of 82%. Seven of these 9 patients exhibited diffuse pericardial 18F-FDG uptake on PET imaging, accompanied by lamellar pericardial thickening on CT. Two patients showed no pericardial 18F-FDG uptake. A significant difference was observed in the duration of symptoms prior to 18F-FDG PET/CT examination between patients with and without pericardial 18F-FDG uptake (Z=-2.15, P = 0.036). Specifically, patients without pericardial 18F-FDG uptake had a notably shorter symptom duration before undergoing 18F-FDG PET/CT (7 days/10 days vs. 40 (30,135) days). In this study, a total of 169 mediastinal lymphadenitis, 16 supraclavicular lymphadenitis, 1 cervical lymphadenitis, and 44 lymphadenitis in other areas were identified. Among the 11 patients, 7 exhibited intrapericardial tuberculosis involvement, primarily affecting the lungs and peritoneum. Conclusions 18F-FDG PET/CT demonstrated high sensitivity in the diagnosis of tuberculous pericarditis. The most common characteristic on 18F-FDG PET/CT was diffuse pericardial 18F-FDG uptake on PET accompanied by lamellar pericardial thickening on CT, which is indicative of tuberculous pericarditis. As a systemic examination, 18F-FDG PET/CT can also detect tuberculosis in other organs, providing complementary diagnostic information for tuberculous pericarditis, thereby facilitating the selection of a more appropriate biopsy site.